Hadiths posted about Imam Ali (peace be upon him) on social media platforms and their impact on society’s behavior - misanjas, misanjas; Jabbar Jassim Ali, Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The distortion in the hadith is considered one of the biggest problems in challenging the Sunnah of the Prophet and the noble hadith, whether the distortion in the hadith was immediately after the time of the text or in this modern time of ours. Due to the seriousness of the situation in changing the original Islamic and doctrinal concepts, this study took it upon itself to reveal this situation in the hadith in our present time and showed its danger and its effects on the behaviors of society, the family, and the individual. The research has developed important results and recommendations that address the process of uncovering this situation and the seriousness of fabrication in the hadith.